2009
DOI: 10.1111/j.1524-4725.2008.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Severe Adverse Reactions To an Injectable Filler Based on a Fixed Combination of Hydroxyethylmethacrylate and Ethylmethacrylate with Hyaluronic Acid

Abstract: Adverse reactions to this methacrylate filler are common. The mean latency period for these mostly severe rated reactions was nearly 2 years. Based on the frequency and severity of these reactions, the use of this filler does not seem to be advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…In the present study, HA were observed to elicit little immune response except when injected in combination with methacrylate. Indeed, some authors recently questioned the use of this type of filler owing to the frequency and severity of adverse reactions (Rossner et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, HA were observed to elicit little immune response except when injected in combination with methacrylate. Indeed, some authors recently questioned the use of this type of filler owing to the frequency and severity of adverse reactions (Rossner et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Although manufacturers and different publications claim that the fillers are non-toxic, non-immunogenic and complications are rare (Engelman et al 2005), unwanted side effects occur with all compounds used (De Boulle 2004;Andre et al 2005;Duffy 2005), as we and others have been able to demonstrate (Alijotas-Reig and García-Giménez 2008; Alcalay et al 2003;Rossner et al 2009). The many different dermal fillers currently available can be classified by product composition (silicone, collagen, hyaluronic acid (HA), poly-l-lactic acid and others) or by the length of time they remain in tissue (temporary, semipermanent or permanent) (Sánchez-Carpintero et al 2010).…”
Section: Introductionmentioning
confidence: 86%
“…A homeostatic action may be assumed to be ideal for an intradermal HA formulation because it will prevent disturbance of the dermal fine structure and still increases volume, hydration and turgor. In contrast, strong evidence has been raised that HA can also function as a danger signal which in turn promotes inflammatory responses, induces angiogenesis and activation of strong migratory and proliferative responses [46] which could lead to hypertrophic scaring, nodule formation and inflammation [45,47,48]. Inflammatory responses that are not due to contaminants are thought to require HA breakdown by Hyal2 to generate small 20-kDa HA fragments from high-molecular-weight HA and possibly further degradation by Hyal1 [49].…”
Section: Discussionmentioning
confidence: 99%
“…These occurrences were overcome in time using bioengineering to synthesize the HA (3-s5,12,15,17,84) . Other currently used filler materials still cause diverse, significant adverse reactions (1,5,17,(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100) , therefore, it is not advisable to combine HA with other materials, or brand names that are not subject to stringent quality controls (1,4-5,84,87,93) .…”
Section: A B C Dmentioning
confidence: 99%